FACTORS AFFECTING THE AREA OF RISK MANAGEMENT DISCLOSURES - Dwiharto, Paulus (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
The purpose of this study was to analyze the effect of leverage, company size, profitability, and auditors on the extent of risk management disclosure. This study uses the population of this study are non-financial companies listed in the 2016 MSCI Indonesia Index for the period of 2016, the research sample used was 68 companies. The data used in this research is secondary data. The data source in this study comes from the website www.ishare.com to find out the data of companies listed in the 2016 MSCI Indonesia Index. The research data used is the company's annual report which can be accessed through the relevant company website or the IDX website at www.idx. co.id. The data analysis method for this research is multiple regression analysis. The results showed that the leverage variable had no significant effect on the extent of risk management disclosure. The results of the leverage test showed that the significance value of leverage was 0.030 (sig